Functional heterogeneity and plasticity in naïve CD8 T cells drive superior effector and memory responses - Yamato Sajiki; Satomi Ando; Charles M. Perkins; Yi-Chung Huang; Katie E. Smith; Carolyn M. Doerning; David A. Hildeman; Koichi Araki (Journal of Experimental Medicine, 2026)
While significant progress has been made in defining subsets among antigen-experienced CD8 T cells, the heterogeneity of naïve CD8 T cells remains poorly understood. Here, we identify naïve CD8 T cell subsets with superior persistence and an enhanced capacity to generate effector and memory cells, leading to more effective protection. These functionally superior naïve CD8 T cells are marked by IL-18Rα, CD73, and CXCR3, and functionally less potent naïve CD8 T cells can convert into these superior subsets through tonic TCR signaling. Their enhanced response to infections is driven by better survival of the progeny effector cells during the T cell expansion phase. This improved survival is mediated by increased Ly6C expression on effector cells derived from these functionally superior naïve cells. Collectively, our findings reveal functional heterogeneity and plasticity among naïve CD8 T cells and uncover a mechanism by which functionally superior naïve subsets drive robust CD8 T cell responses, providing a previously unrecognized layer of immune regulation.